The Development Pengembangan E-LKPD Berbasis Google Sites Dengan Integrasi Budaya “Njeleng” pada Materi Hakikat dan Peranan Ilmu Kimia - Sura Juddin; Muti'ah Muti'ah; Eka Junaidi (Chemistry Education Practice, 2026)
This research aims to develop an electronic Student Worksheet (e-LKPD) based on Google Sites that integrates the local culture "Njeleng" into the subject matter of the nature and introduction of chemistry. The development of this learning media is expected to increase students' interest and understanding of chemistry through a contextual and cultural approach. The research method employed is the four-D (4D) model consisting of the stages of needs analysis, design, development, and product evaluation. The developed e-LKPD product was tested on students and validated by experts to determine its validity and practicality. The results indicated that the Google Sites-based e-LKPD with the integration of "Njeleng" culture achieved an average validity score of 0.78, demonstrating that the media is valid as a teaching resource. Additionally, practicality tests showed an average score of 80%, indicating ease of use by both teachers and students during the learning process. The incorporation of local culture as a learning context adds value in cultural preservation while enriching students' learning experiences. Therefore, this e-LKPD is recommended as an innovative and relevant alternative learning media tailored to student characteristics, capable of enhancing enthusiasm and comprehension of basic chemistry concepts.